(untitled) (Global Journal of Management and Business Research, 2024)
Summary- Artificial Intelligence AI is driving a significant and positive change in how businesses operate fundamentally changing established models and pushing enterprises towards a more efficient and innovative future This concise abstract explores the intricate influence of artificial intelligence AI on several aspects of corporate operations It thoroughly analyses the development and present uses of AI as well as successful cases obstacles and forthcoming trends 1 An Examination of the Role of Artificial Intelligence AI in the Operations of Businesses The introduction provides a comprehensive overview of the development of AI and its incorporation into business operations The text explores the role of AI in transforming decision-making processes highlighting its versatility in optimizing operations across various industries It covers topics such as automation and predictive analytics 2 Artificial Intelligence AI is being Increasingly Utilized in Several Aspects of Business Operations An extensive examination of AI applications includes the enhanced efficiency of automation the predictive capabilities of analytics the transformative influence of AI in Customer Relationship Management CRM and its effects on Supply Chain Management The passage emphasizes the essential role of AI in improving operational efficiency 3 Examples of Successful Implementation of Artificial Intelligence Case studies are used to demonstrate real-world applications namely how large companies utilize artificial intelligence AI for tailored suggestions optimizing industrial processes and detecting fraud in financial institutions These stories emphasize the concrete advantages that AI provides to many industries